Isolation, characterization and antibiotic sensitivity pattern of bacteria associated with respiratory tract diseases of pigs - Rajkhowa, S; Devi, Mrinalee; Das, Anubrata (The Indian Journal of Animal Sciences, 2012)
The study was conducted to isolate the aerobic bacterial pathogens associated with respiratory diseases of pigs. The bacteria isolated from the pigs affected with respiratory diseases were Pasteurella multocida, Bacillus subtilis, Streptococcus suis, Staphylococcus aureus, Klebsiella pneumoniae and Micrococcus spp. All the isolates of P. multocida were found sensitive to chloramphenicol, chlortetracycline, ciprofloxacin, doxycillin, enrofloxacin and gentamicin whereas isolates were resistant to cephalexin, penicillin G and sulphadiazine. The isolates of Staphylococcus aureus showed highest sensitivity to amikacin, chloramphenicol and gentamicin and lowest sensitivity to penicillin, sulphadizine and tetracycline. Isolates of Streptococcus suis showed higher sensitivities to amikacin, enrofloxacin, gentamicin and penicillin and resistance to ceftriaxone, cephalexin, terracycline and sulphadizine. All the isolates of Bacillus subtilis were sensitive to majority of the antimicrobials tested in the study and Micrococcus species were highly sensitive to amikacin, chlortetracycline, enrofloxacin and gentamicin.